Impact of a Multimodal Antimicrobial Stewardship Program on Pseudomonas aeruginosa Susceptibility and Antimicrobial Use in the Intensive Care Unit Setting - Douglas Slain; Arif R. Sarwari; Karen O. Petros; Richard L. McKnight; Renee B. Sager; Charles J. Mullett; Alison Wilson; John G. Thomas; Kathryn Moffett; H. Carlton Palmer; Harakh V. Dedhia (Critical Care Research and Practice)
Objective. To study the impact of our multimodal antibiotic stewardship program on Pseudomonas aeruginosa susceptibility and antibiotic use in the intensive care unit (ICU) setting. Methods. Our stewardship program employed the key tenants of published antimicrobial stewardship guidelines. These included prospective audits with intervention and feedback, formulary restriction with preauthorization, educational conferences, guidelines for use, antimicrobial cycling, and de-escalation of therapy. ICU antibiotic use was measured and expressed as defined daily doses (DDD) per 1,000 patient-days. Results. Certain temporal relationships between antibiotic use and ICU resistance patterns appeared to be affected by our antibiotic stewardship program. In particular, the ICU use of intravenous ciprofloxacin and ceftazidime declined from 148 and 62.5 DDD/1,000 patient-days to 40.0 and 24.5, respectively, during 2004 to 2007. An increase in the use of these agents and resistance to these agents was witnessed during 2008–2010. Despite variability in antibiotic usage from the stewardship efforts, we were overall unable to show statistical relationships with P. aeruginosa resistance rate. Conclusion. Antibiotic resistance in the ICU setting is complex. Multimodal stewardship efforts attempt to prevent resistance, but such programs clearly have their limits.